2011
DOI: 10.1063/1.3626406
|View full text |Cite
|
Sign up to set email alerts
|

Mean velocity and length-scales in the overlap region of wall-bounded turbulent flows

Abstract: The length scales of the spectra and correlation functions of the velocity fluctuations in the overlap region of turbulent wall-bounded flows are analyzed. It is found that a mixing length based on the mean local shear works better as a normalization than the distance to the wall. To define an overlap range sufficiently long and independent of the Reynolds number to allow the two scalings to be tested, the classical asymptotic expansion of the mean shear is extended to include a near-wall virtual origin and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…For example, by using an iterative curve-fitting procedure, Mizuno & Jimenez (2011) demonstrate that for the δ + = 2004 flow of figure 7 their modified mixing length model exhibits its optimal behaviour over a domain that extends from ∼100 y + 1100. The present theoretical prediction indicates that the onset of the self-similarity associated with A(β) const.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, by using an iterative curve-fitting procedure, Mizuno & Jimenez (2011) demonstrate that for the δ + = 2004 flow of figure 7 their modified mixing length model exhibits its optimal behaviour over a domain that extends from ∼100 y + 1100. The present theoretical prediction indicates that the onset of the self-similarity associated with A(β) const.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis went up to δ + 8500 in the boundary layer and δ + 4000 in the channel. The offset appears in the formula of Mizuno & Jimenez (2011) owing to their use of a higher-order approximation. This is distinct from the overlap-layer-based arguments of Spalart et al (2008) and Wosnik et al (2000), which portray the offset as part of the leading-order equation.…”
Section: Elements Of the Channel And Pipe Flow Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The key in answering this question can be found from previous findings where the spanwise length scale of energy-containing motions in the logarithmic region is shown to be linearly proportional to the distance from the wall (Tomkins & Adrian 2003;delÁlamo et al 2004;Ganapathisubramani et al 2005;Hutchins et al 2005). We note that recent investigations have shown that the local mixing length scale defined by l(y) = u τ (dU/dy) −1 provides a better length scale for the logarithmic region (Mizuno & Jiménez 2011;Pirozzoli 2012), but this mixing length scale also gives the linear growth of the spanwise length scale at least at the leading-order, specially if the logarithmic behaviour becomes evident as for the flows at sufficiently high Reynolds numbers.…”
Section: Computing Attached Eddies At a Given Length Scalementioning
confidence: 94%
“…A more conservative definition of the logarithmic layer, in terms of the mean velocity profile, only extends to y/h ≈ 0.15, especially in boundary layers (Nagib et al 2006), but that outer limit is mostly due to the relatively strong 'wake' component of the mean velocity profile in external flows, which is a consequence of the rotational-irrotational intermittency along the edge of the boundary layer ). The wake is much weaker in internal flows, and it was shown by Mizuno & Jiménez (2011) that the logarithmic fit of the mean profile can be extended in channels to y/h ≈ 0.5 by a simple modification of the classical law. Moreover, neither the logarithmic mean profile nor the linear spectral scaling will be particularly important in most of the following.…”
Section: The Numerical Experimentsmentioning
confidence: 99%